2012
DOI: 10.5625/lar.2012.28.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo bilobaextract (EGb 761) prevents the ischemic brain injury-induced decrease in parvalbumin expression

Abstract: Ginkgo biloba extract (EGb 761) exerts a neuroprotective effect against ischemic brain injury through an anti-apoptotic mechanism. Parvalbumin is a calcium buffering protein that plays an important role in modulating intracellular calcium concentration and regulating apoptotic cell death. The aim of this study was to investigate whether EGb 761 affects parvalbumin expression in cerebral ischemic injury. Adult male Sprague-Dawley rats were treated with vehicle or EGb 761 (100 mg/kg) prior to middle cerebral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…EGb 761 is an effective antioxidant that has been shown to provide protection against cardiovascular and neurological disorders [31, 32]. Many groups, including ours, have previously shown that EGb 761 attenuates brain damage in male rodents after permanent, transient and global models of ischemia [15, 16, 33]. The neuroprotective properties of EGb 761 are mainly attributed to HO1 induction, and we have shown the synergistic effect of EGb 761 in attenuating brain damage by upregulating the HO1/Wnt pathway and inducing neurogenesis in male mice [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…EGb 761 is an effective antioxidant that has been shown to provide protection against cardiovascular and neurological disorders [31, 32]. Many groups, including ours, have previously shown that EGb 761 attenuates brain damage in male rodents after permanent, transient and global models of ischemia [15, 16, 33]. The neuroprotective properties of EGb 761 are mainly attributed to HO1 induction, and we have shown the synergistic effect of EGb 761 in attenuating brain damage by upregulating the HO1/Wnt pathway and inducing neurogenesis in male mice [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…As a huge influx of calcium into the cell activates downstream pathways of ischemia-reperfusion injury, Koh et al [ 72 ] found that EGb 761 could prevent the decrease in the level of hippocalcin, a sensor of neuronal intracellular calcium concentration, to confer neuroprotection. Parvalbumin, another calcium buffering protein, was reported to decrease after ischemia, but EGb 761 was found to reverse this effect [ 73 ].…”
Section: The Effect Of Egb On Aging-related Diseasesmentioning
confidence: 99%
“…У крыс, получавших EGb761, отмечалось менее зна-чительное снижение экспрессии парвальбумина. Это ис-следование позволило обнаружить еще один механизм нейропротективного и антиапоптотического действия EGb761 -поддержание нормальной экспрессии парваль-бумина в ишемизированном мозге [27].…”
Section: цереброваскулярные заболеванияunclassified